Pengaruh Ukuran Perusahaan, Audit Tenure Dan Financial Distress Terhadap Kualitas Audit - Novi Mulyani; Sasmita Sari Ardaninggar (GLOBAL SCIENTS PUBLISHER, 2025)
This research aims to analyze and obtain empirical evidence about the influence of company size, audit tenure, and financial distress on audit quality in industrial sector companies in Indonesia. The research sample is industrial sector companies listed on the Indonesia Stock Exchange (BEI) for the period 2018 - 2023. The type of research used is quantitative research, and the type of data used is secondary data. Data collection was carried out using the purposive sampling method. The number of companies sampled was 13 companies with 78 financial report data and company annual reports. Data processing uses eviews 12 with the analysis method for this research using logistic regression. The results of this research show that based on the statistical z test, company size partially has a positive effect on audit quality, audit tenure partially has no significant effect on audit quality, partial financial distress has no significant effect on audit quality. Based on the Simultaneous LR test, it shows that company size, audit tenure, and financial distress simultaneously influence audit quality.